Primnoidae (Cnidaria: Octocorallia) of the SW Indian Ocean: new species, genus revisions and systematics - Taylor, M; Rogers, A (Oxford University Press, 2017)
The Indian Ocean is one of the least-studied areas of the world’s largest biome, the deep sea. On an expedition to five seamounts along the SW Indian Ocean Ridge in 2011, thousands of specimens from deep-sea habitats were procured. We propose five new species of Primnoidae, a predominantly deep-sea octocoral family. The new species include three from the genus Narella, and one new species each from Primnoa and Primnoeides; the latter genus is revised and we propose Digitogorgia as its junior synonym. We support the new species placement within Primnoidae through taxonomic descriptions and the most comprehensive molecular phylogenetic analysis of any deep-sea coral family (81 species across 29 genera). We also present a rare example of polar submergence (from the Antarctic shelf into deeper waters).